2006
DOI: 10.1002/pssb.200671518
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor quantum dots devices: Recent advances and application prospects

Abstract: In this paper, a brief review will be given on recent advances in semiconductor quantum dots based optoelectronic devices. The focus will be on two major application areas, i.e., telecom devices and high power light sources, where some device examples will be discussed on the current status and for the future prospects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Perhaps the most important contributions have been made for optoelectronic systems. Taking advantage of quantummechanical effects, these new devices are able to control many properties of macroscopic materials [1].…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most important contributions have been made for optoelectronic systems. Taking advantage of quantummechanical effects, these new devices are able to control many properties of macroscopic materials [1].…”
Section: Introductionmentioning
confidence: 99%
“…If luminescence is the desired detection signal, then inorganic nanocrystals or quantum dots (QDs) are a preferred chemosensing scaffold, owing to their unique photophysical properties. Typically, the luminescence of suitably prepared QDs is unperturbed by changes in their environment (i.e., luminescence is constant in both the presence and absence of analyte), affording a suitable framework for ratiometric sensing, which relies on signal changes relative to an internal standard to quantify the amount of analyte.…”
Section: Introductionmentioning
confidence: 99%
“…30,51,63 Fischbeck et al 64 reported the first polymer waveguide using Nanocrystals and clusters such as quantum dots (QDs) are chemically synthesized semiconducting nanometer-sized crystalline particles, which exhibit unique optical and spectroscopic properties, such as broad absorption, narrow and tunable emission, resistance to photobleaching, efficient luminescence, and long luminescent lifetimes. 72 They are promising building blocks for a range of photonic applications, [73][74][75] as well as the immerging fields of medicinal and biological imaging applications. 76 While the particles easily disperse in various solvents, to utilize their functionality in practical integrated photonic systems, they need to be encapsulated into a more robust but highly functional matrix.…”
Section: Applications Photonicsmentioning
confidence: 99%